Placenta accreta/increta/percreta: incidence, risk factors, management and outcomes. (18th April 2012) - Fitzpatrick, KE; Sellers, S; Spark, P; Kurinczuk, JJ; Brocklehurst, P; Knight, M
Abstract : Objective: To estimate the incidence and describe the risk factors, management and outcomes of placenta accreta/increta/percreta. Methods: A national population-based case-control study was undertaken using the UK Obstetric Surveillance System between May 2010-April 2011. Participants comprised 134 women with placenta accreta/increta/percreta and 258 controls. Results: The estimated incidence of placenta accreta/increta/percreta was 1.7 per 10, 000 maternities (95%CI 1.4-2.0). Older women had raised odds of having placenta accreta/increta/percreta (aOR 3.3, 95%CI 1.4-7.6 in women 35+yrs) as did women who had a previous caesarean (aOR 14.2, 95%CI 5.5-36.5), other previous uterine surgery (aOR 2.8, 95%CI 1.1-7.7), placenta praevia diagnosed antepartum (aOR 69.5, 95%CI 17.7–273.0) and an IVF pregnancy (aOR 43.8, 95%CI 2.7–699.5). Placenta accreta/increta/percreta was suspected in 50% of women antenatally. Of the 27(20%) women who had their complete placenta left in situ, 15(56%) had a hysterectomy. Of the 107(80%) women who did not have their complete placenta left in situ, 63(59%) had a hysterectomy. Overall, 61% had other therapies to treat haemorrhage prior to hysterectomy and 5% had methotrexate used. There were no maternal deaths, but women with placenta accreta/increta/percreta were more likely to deliver preterm (aOR 16.9, 95%CI 7.5–38.1) and 70% were admitted to ITU/HDU. Conclusions: Placenta accreta/increta/percreta is uncommon but associated with preterm delivery and significant maternal morbidity. This study confirms previously reported associations including with prior caesarean delivery; the association with IVF pregnancy requires confirmation in other studies. Treatment varied and further investigation of the clinical effectiveness of different management strategies is warranted.